Rubia hangii (Rubiaceae), a new species from Guangxi Province, China - Yang, Li-E; Meng, Ying; Zhou, Zhuo; Nie, Ze-Long (Phytotaxa, 2017)
Rubia hangii, a new species of Rubia sect. Oligoneura from Guangxi Province, China, is described and illustrated. The placement of this species within Rubia is assessed based on a molecular phylogenetic analysis and morphological comparisons with related species. The new species is morphologically similar to R. siamensis and R. falciformis, but differs from the two taxa in having membranous to thin papery leaf blade, margins flat , slender petiole (< 1 mm wide), ovate-lanceolate stipule, triangular corolla lobes, fruit glabrous, with 1 ovule often aborted and 1 mericarp developed, rarely with 2 mericarps. Molecular phylogenetic analyses suggested that R. hangii is closely related to R. argyi and R. pallida. Rubia hangii can be easily distinguished from R. argyi and R. pallida based on leaf and stipule arrangement, leaf shape, number of principal veins, inflorescence position and flower shape.